2008
DOI: 10.1134/s102279540804008x
|View full text |Cite
|
Sign up to set email alerts
|

Length variation of i-type low-molecular-weight glutenin subunit genes in diploid wheats

Abstract: -Allelic variation of the low-molecular-weight glutenin subunit (LMW-GS) is associated with the significant differences of dough quality in bread and durum wheat, and has been widely evaluated at protein level in wheat and its relatives. In this study, a PCR primer set, targeting the high variable repetitive domains, was employed to assay the length variation of i-type LMW-GS genes in the A-genomes of diploid wheats, the diploid progenitors of tetraploid and hexaploid wheat. A total of 71 accessions of diploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The i-type genes were reported only at the Glu-A3 locus (Zhang et al ., 2004; Ikeda et al ., 2006; Huang and Cloutier, 2008; Dong et al ., 2010; Wang et al ., 2010; Zhang et al ., 2011 a , b ) or the A genome, for example T. urartu and T. monococcum (An et al ., 2006; Ma et al ., 2006; Caballero et al ., 2008; Long et al ., 2008). The findings also indicate that all i-type genes detected in MCC accessions were located at the Glu-A3 locus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The i-type genes were reported only at the Glu-A3 locus (Zhang et al ., 2004; Ikeda et al ., 2006; Huang and Cloutier, 2008; Dong et al ., 2010; Wang et al ., 2010; Zhang et al ., 2011 a , b ) or the A genome, for example T. urartu and T. monococcum (An et al ., 2006; Ma et al ., 2006; Caballero et al ., 2008; Long et al ., 2008). The findings also indicate that all i-type genes detected in MCC accessions were located at the Glu-A3 locus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant variability of storage proteins in T. urartu , was detected in gliadin proteins and HMW-GSs using electrophoretic procedures or nucleotide sequence analysis [ 29 , 30 ]. Several variants with repetitive domain length polymorphism were also observed in LMW-GS genes [ 31 ]. However, the detailed composition and genetic diversity of LMW-GS genes in T. urartu remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The loci of HMW-GS (Glu-A1, Glu-B1 and Glu-D1) and LMW-GS (Glu-A3, Glu-B3 and Glu-D3) subunits are located on the long and short arms, respectively [69]. In one of the largest studies on the effect of glutenins on wheat quality, it was reported that Glu-B1, Glu-D1, and Glu-B3 loci have the greatest effect on glutenin variations compared to other loci [8,[70][71][72]. In addition to GPC, several MTAs that have a significant relationship with baking quality (mixograph mixing and bake mixing times) can be used in MAS due to their tight linkage with glutenin and gliadin loci [61].…”
Section: Marker-assisted Selection (Mas) and Its Applications In Impr...mentioning
confidence: 99%